A small molecule inhibitor of PCSK9 that antagonizes LDL receptor binding via interaction with a cryptic PCSK9 binding groove. Issue 6 (15th March 2020) - Evison, Benny J.; Palmer, James T.; Lambert, Gilles; Treutlein, Herbert; Zeng, Jun; Nativel, Brice; Chemello, Kévin; Zhu, Qing; Wang, Jie; Teng, Yanfen; Tang, Wei; Xu, Yanfeng; et al.
Graphical abstract: Abstract: Proprotein convertase (PC) subtilisin kexin type 9 (PCSK9) inhibits the clearance of low density lipoprotein (LDL) cholesterol from plasma by directly interacting with the LDL receptor (LDLR). As the interaction promotes elevated plasma LDL cholesterol levels and a predisposition to cardiovascular disease (CVD), it has attracted much interest as a therapeutic target. While anti-PCSK9 monoclonal antibodies have been successful in the treatment of hypercholesteremia by decreasing CVD risk, their high cost and a requirement for injection have prohibited widespread use. The advent of an orally bioavailable small molecule inhibitor of the PCSK9-LDLR interaction is an attractive alternative, however efforts have been tempered as the binding interface is unfavourable for binding by small organic molecules. Despite its challenging nature, we report herein the discovery of compound 3f as a small molecule inhibitor of PCSK9. The kinase inhibitor nilotinib emerged from a computational screen that was applied to identify compounds that may bind to a cryptic groove within PCSK9 and proximal to the LDLR-binding interface. A subsequent in vitro PCSK9-LDLR binding assay established that nilotinib was a bona fide but modest inhibitor of the interaction (IC50  = 9.8 µM). Through multiple rounds of medicinal chemistry, 3f emerged as a lead-like molecule by demonstrating disruption of the PCSK9-LDLR interaction at nanomolar levels in vitro (IC50  = 537 nM) with no inhibitory activity (IC50  > 10 µM) against a small panel of kinases. Compound 3f restored LDL uptake by liver cells at sub-micromolar levels and demonstrated excellent bioavailability when delivered subcutaneously in mice. Most significantly, compound 3f lowered total cholesterol levels in the plasma of wild-type mice, thereby providing proof-of-concept that the notion of a small molecule inhibitor against PCSK9 is therapeutically viable.